Prostate Biopsy Interpretation: An Illustrated Guide - Shah, Rajal B.; Zhou, Ming.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Prostate needle biopsy specimens account for an important portion of a surgical pathologist$1 (Bs daily work. There is, however, a significant error rate when diagnosing prostate cancer in needle biopsies. Furthermore, the modified Gleason grading scheme is being only slowly adopted, and there is considerable variation in reporting. This book covers all the practical issues related to the interpretation of prostatic biopsies in day-to-day practice, including: biopsy sampling and processing; the diagnosis of limited cancer; differentiation of prostate cancers from benign lesions and recognition of histologic variants; the recognition and clinical significance of (3z(Batypical(3y (Bdiagnoses and HGPIN; the identification of recently described entities; the contemporary approach to Gleason grading; the utility of immunohistochemical markers and emerging molecular markers; and the reporting of prostate biopsies. The book contains numerous carefully selected, high-quality color images and uses algorithms, flow charts, and tables to simulate the thought and decision-making process upon encountering common clinical scenarios during sign-out of prostate biopsy. It will appeal especially to practicing surgical pathologists as well as to pathology residents and fellows in training who require a handy resource designed for use in daily practice.s
Anatomy and Normal Histology of the Prostate Pertinent to Biopsy Practice -- Prostate Needle Biopsy Sampling Techniques: Impact on Pathological Diagnosis -- Diagnosis of Limited Cancer in Prostate Biopsy -- Immunohistochemistry in Prostate Biopsy Evaluation -- Contemporary Approach to Gleason Grading of Prostate Cancer -- Histologic Variants of Prostate Carcinoma -- Benign Mimics of Prostate Carcinoma -- Atypical Cribriform Lesions in Prostate Biopsy: Relationship to Prostate Carcinoma, Differential Diagnosis, and Emerging Concepts of Intraductal Carcinoma of the Prostate -- High-Grade Prostatic Intraepithelial Neoplasia -- Atypical Glands Suspicious for Cancer -- Spindle Cell Lesions of the Prostate Gland -- Treatment Effect in Benign and Malignant Prostate Tissue -- Molecular Biology of Prostate Cancer and Emerging Diagnostic and Prognostic Biomarkers -- Biopsy Specimen Handling, Processing, Quality Assurance Program -- Reporting of Prostate Biopsy.
Keywords: Medicine; Pathology; Urology; Medicine & Public Health; Pathology; Urology/Andrology.